"Owner`s manual for personality at work : how the big five personality traits affect performance, communication, teamwork, leadership, and sales" - "Howard, Pierce J." (USA, 2010)
This book covers the WorkPlace Big Five Profile supertraits, subtraits and competencies that describe how people respond to stress, adjust to their environment, determine interests, work with others, and establish their roles and goals. It includes workplace case studies and useful applications in areas such as: leadership, job profiling and selection, education and training, coaching, career planning, teamwork, and after-hours applications.